Juvenile Myelomonocytic Leukemia in Turkey: A Retrospective Analysis of Sixty-five Patients - KOÇ, AHMET (GALENOS YAYINCILIK, 2018)
Objective: This study aimed to define the status of juvenile myelomonocytic leukemia (JMML) patients in Turkey in terms of time of diagnosis, clinical characteristics, mutational studies, clinical course, and treatment strategies. Materials and Methods: Data including clinical and laboratory characteristics and treatment strategies of JMML patients were collected retrospectively from pediatric hematology-oncology centers in Turkey. Results: Sixty-five children with JMML diagnosed between 2002 and 2016 in 18 institutions throughout Turkey were enrolled in the study. The median age at diagnosis was 17 months (min-max: 2-117 months). Splenomegaly was present in 92% of patients at the time of diagnosis. The median white blood cell, monocyte, and platelet counts were 32.9x10(9)/L, 5.4x10(9)/L, and 58.3x10(9)/L, respectively. Monosomy 7 was present in 18% of patients. JMML mutational analysis was performed in 32 of 65 patients (49%) and PTPN11 was the most common mutation. Hematopoietic stem cell transplantation (HSCT) could only be performed in 28 patients (44%), the majority being after the year 2012. The most frequent reason for not performing HSCT was the inability to find a suitable donor. The median time from diagnosis to HSCT was 9 months (min-max: 2-63 months). The 5-year cumulative survival rate was 33% and median estimated survival time was 30 +/- 17.4 months (95% CI: 0-64.1) for all patients. Survival time was significantly better in the HSCT group (log-rank p=0.019). Older age at diagnosis (>2 years), platelet count of less than 40x10(9)/L, and PTPN11 mutation were the factors significantly associated with shorter survival time. Conclusion: Although there has recently been improvement in terms of definitive diagnosis and HSCT in JMML patients, the overall results are not satisfactory and it is necessary to put more effort into this issue in Turkey.
Keywords: Hematopoietic stem cell transplantation; Juvenile myelomonocytic leukemia; Turkey; PEDIATRIC MYELODYSPLASTIC SYNDROMES; BONE-MARROW-TRANSPLANTATION; STEM-CELL TRANSPLANTATION; RAS MUTATIONS; CBL MUTATIONS; WORKING-GROUP; CHILDHOOD; CHILDREN; NEUROFIBROMATOSIS; CLASSIFICATION